2022
DOI: 10.1155/2022/1828473
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment Neutrophil-to-Lymphocyte Ratio and Lactate Dehydrogenase Predict the Prognosis of Metastatic Cervical Cancer Treated with Combination Immunotherapy

Abstract: Background. Immune checkpoint inhibitors have considerably changed the treatment paradigm for metastatic cervical cancer; nonetheless, only a proportion of patients achieve a durable response. Therefore, exploring the predictive biomarkers of immunotherapy response is of crucial importance. This study aimed to evaluate the predictive and prognostic value of hematological parameters in patients with metastatic cervical cancer treated with combination immunotherapy. Methods. Clinical data of patients with metast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 45 publications
0
12
2
Order By: Relevance
“…We also found that the baseline CAR was a significant and independent prognostic factor for PFS and OS, as patients with elevated CAR had a short PFS and OS after tislelizumab therapy. However, the pretreatment NLR showed no significant association with the response to PD-1 inhibitors or PFS, which was in contrast to the results of a previous study ( 20 ) and warrants further investigation. Overall, pretreatment serum CRP and CAR levels may be the promising biomarkers for predicting the response to treatment and prognosis of R/M CC patients treated with PD-1 inhibitors.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…We also found that the baseline CAR was a significant and independent prognostic factor for PFS and OS, as patients with elevated CAR had a short PFS and OS after tislelizumab therapy. However, the pretreatment NLR showed no significant association with the response to PD-1 inhibitors or PFS, which was in contrast to the results of a previous study ( 20 ) and warrants further investigation. Overall, pretreatment serum CRP and CAR levels may be the promising biomarkers for predicting the response to treatment and prognosis of R/M CC patients treated with PD-1 inhibitors.…”
Section: Discussioncontrasting
confidence: 99%
“…Routine blood tests can indicate the state of inflammation and nutrition, which have been reported to affect the efficacy of immunotherapy ( 38 ) and have the advantages of being easily available and cost-effective. One study assessed the relationship between immunotherapy and hematological parameters, namely NLR, PLR, MLR, albumin-to-globulin ratio, alkaline phosphatase and lactate dehydrogenase (LDH) in CC patients, and found that high pretreatment NLR and LDH were independently correlated with poor survival ( 20 ). Thus, the predictive value of hematological parameters, especially those reflecting the inflammatory and nutritional status of patients with CC receiving PD-1 inhibitors, merits further study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, in cervical cancer, studies have shown that an increased NLR is associated with poor prognosis of cervical cancer [ 21 , 22 ]. Cheng’s study [ 23 ] suggested that high pretreatment NLR values were independently correlated with poor survival in patients with metastatic cervical cancer treated with combination immunotherapy. Therefore, whether controlling the dose of BM irradiation and reducing the NLR can improve the prognosis of patients with cervical cancer needs further study.…”
Section: Discussionmentioning
confidence: 99%
“…Blood cell parameters such as neutrophil-to-lymphocyte, platelet-to-lymphocyte and lymphocyte-to-monocyte ratios (NLRs, PLRs and LMRs, respectively) are predictive markers of therapeutic effects and survival rates among patients with various types of cancer treated with ICIs. [11][12][13][14][15][16][17][18] However, to the best of our knowledge, correlations among blood parameters, therapeutic effects and survival have not been fully evaluated in patients with ESCC under nivolumab monotherapy. Here, we evaluated the ability of various clinical factors, including NLR, PLR and LMR, to predict therapeutic effects and survival in patients with unresectable advanced or recurrent ESCC treated with second-or laterline nivolumab monotherapy.…”
Section: Introductionmentioning
confidence: 99%